(Re-)activity in the caregiving situation: Genetic diversity within Oxytocin–Vasopressin Pathway is associated with salivary oxytocin and vasopressin concentrations in response to contact with a crying infant-simulator. (September 2021) - Rybicka, Magda; Kaźmierczak, Maria; Pawlicka, Paulina; Łada-Maśko, Ariadna Beata; Anikiej-Wiczenbach, Paulina; Bielawski, Krzysztof Piotr
Abstract: Oxytocin (OT) and vasopressin (AVP) hormones as well as their receptors (OXTR and AVPR1a) have been deemed crucial for caregiving and sensitive responsiveness to infant cues. However, previous research on genetic polymorphisms and OT and AVP levels in the context of caregiving were sparse and have brought contradictory findings. The aim of this reported observational study was to examine the impact of genetic variations within genes related to OT and AVP signaling pathway on hormones levels' changes in response to the caregiving situation. A total of 221 adult intimate couples (110 childless, non-pregnant and 111 expectant couples) participated in three 10 min sessions, during which they were taking care of a crying life-like simulator. 30 min prior to the first session salivary samples to analyze basal OT and AVP, and polymorphisms in OXTR, AVPR1a and CD38 genes were collected. Subsequent OT and AVP levels were measured 15 min after each session. The two most frequently studied OXTR SNPs (rs53576 and rs2254298) had no or a minor impact on higher OT levels, which were linked to rs1042778, rs13316193, rs2228485, rs2268490, rs4686302 genotypes. AVP levels were affected by rs1042778, rs13316193, rs4686302 and rs237887. OT levels varied depending on the OT (rs2770378, rs4813625), CD38 (rs379686), and 5-HTR2A (rs6314) genotype. OT and AVP levels were also associated with rs6314 ( 5-HTR2A ). AVP levels were linked to ESR1 (rs1884051) and SIM1 (rs3734354) variations. Shorter variants of RS3 and RS1 were associated with lower levels of AVP. In conclusion, analyzed polymorphisms were associated with both the level and changes in OT and AVP hormone levels in the standardized situation of caregiving reactions to infant crying. Highlights: SNPs within OT and AVP related genes shaped both their level and changes in saliva in the standardized caregiving situation. Salivary OT was linked to oxytocin-related polymorphisms (e.g. within OXTR, OT, CD38 ) and to functional rs6314 ( 5-HTR2A ). Salivary AVP was linked to OT and AVPR1a SNPs, but also to rs6314 ( 5-HTR2A ), and to ESR1 and SIM1 polymorphisms.